Preferential CO2 Separation over H2 with Poly(amidoamine) Dendrimer-Containing Polymeric Membrane. Issue 1660 (28th March 2014) - Taniguchi, Ikuo; Fujikawa, Shigenori
ABSTRACT: Development of effective CO2 separation technologies is one of the most critical issues for implementation of CO2 Capture & Storage (CCS) because CO2 capturing covers about 60 % of the total CCS cost. CO2 capturing with solution absorption technology has gained current acceptance, and the actual operations have been demonstrated in many countries. However, This technology requires certain amount of energy in recovering CO2 from the CO2 -capturing solution, which results in developing alternative CO2 capturing technologies. Because difference in partial pressure of the interest gas between feed and permeate side drives the separation, membrane separation does not need additional energy and can make CO2 separation much more effective. ☐In pre-combustion such as an integrated gasification combined cycle (IGCC) plant, CO2 /H2 gas mixture after water-gas shift reaction has a pressure of 2.4 MPa, which would be preferable for membrane separation. Various membranes for CO2 separation over H2 have been investigated, however, the membrane separation has not been implemented due to lack in CO2 selectivity or permeability. In this paper, poly(amidoamine) (PAMAM) dendrimer is used to enhance affinity to CO2 and incorporated in a polymer matrix. The resulting polymeric membrane expressed excellent CO2 separation properties even under pressure. The CO2 permeance is relatively lower than the requirement value and 1.0 x 10 -10 m 3 (STP)/(m 2 s Pa). However, the permeance can be enhanced by reducing membrane thickness.